Traveller's diarrhoea with a vengeance in children of UK immigrants visiting their parental homeland. Issue 3 (March 1982) - Hutchins, P; Hindocha, P; Phillips, A; Walker-Smith, J
Abstract : Six healthy children, born in the UK, travelled to their parental homeland and developed a severe form of traveller's diarrhoea. This was characterised by rapid loss of weight and chronic diarrhoea. On return to this country, investigation in 5 of them showed an abnormal, small intestinal mucosa. There was a high incidence of pathogens and potential pathogens found in stools and duodenal juice. Immunodeficiency was found in 2 of them. Small intestinal mucosal damage related to gut infection in previously well children appears to be of cardinal importance in the interaction between chronic diarrhoea and malnutrition. This observation may point the way to future research into the primary role of gut infection in the initiation of the cycle of malnutrition and chronic diarrhoea in developing communities.